2020
DOI: 10.5114/wo.2020.102631
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic challenge in pulmonary tumour embolism in cancer: a case report and literature review

Abstract: Pulmonary tumour embolism is a rare condition without specific symptoms or pathognomonic features. Pulmonary tumour embolism can occur as the first manifestation of cancer, but because of diagnostic difficulties, it is often wrongly recognised as a more common cardiopulmonary disease. We present a case of a 46-year-old Caucasian male with no prior malignancy diagnosis, admitted because of progressing dyspnoea and cough. Based on radiological and clinical presentations, sarcoidosis, silicosis and lymphangitic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the retrospective analysis, narrowing of the unilateral pulmonary vessels with or without lobar volume loss in the left lung was identified in 100% of the patients. Narrowing of unilateral pulmonary vessels with volume loss can generally be caused by chronic reductions in pulmonary arterial inflow due to congenital disorders or tumor embolism (14)(15)(16). Recently, Goitein et al reported that contrast-enhanced CT showed narrowing of the pulmonary arteries (oligemia), volume loss and mediastinal collaterals in patients with severe PVS after CA for AF (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the retrospective analysis, narrowing of the unilateral pulmonary vessels with or without lobar volume loss in the left lung was identified in 100% of the patients. Narrowing of unilateral pulmonary vessels with volume loss can generally be caused by chronic reductions in pulmonary arterial inflow due to congenital disorders or tumor embolism (14)(15)(16). Recently, Goitein et al reported that contrast-enhanced CT showed narrowing of the pulmonary arteries (oligemia), volume loss and mediastinal collaterals in patients with severe PVS after CA for AF (11).…”
Section: Discussionmentioning
confidence: 99%